Znaczenie i możliwości poprawy precyzji rachunku wartości bieżącej i przyszłej strumienia dochodów przedsiębiorstwa - Wrzosek, Stefan (The Importance and Ways to Improve Precision of Present and Future Values of Stream of Enterprise Profits Calculation, 2007)
The paper shows that using a rule of payments at the beginning or at the end of the periods in some economical calculations (like NPV) is not an error, while in others (like income-based valuation) usually is. It is suggested to reduce this error by using payments in the middle of the periods or in case of seasons in other moments of periods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 462-467